The journey of preproteins across the chloroplast membrane systems - Ballabani, Gent; Forough, Maryam; Kessler, Felix; Shanmugabalaji, Venkatasalam (Frontiers in Physiology, 2023)
The photosynthetic capacity of chloroplasts is vital for autotrophic growth in algae and plants. The origin of the chloroplast has been explained by the endosymbiotic theory that proposes the engulfment of a cyanobacterium by an ancestral eukaryotic cell followed by the transfer of many cyanobacterial genes to the host nucleus. As a result of the gene transfer, the now nuclear-encoded proteins acquired chloroplast targeting peptides (known as transit peptides; TP) and are translated as preproteins in the cytosol. Transit peptides contain specific motifs and domains initially recognized by cytosolic factors followed by the chloroplast import components at the outer and inner envelope of the chloroplast membrane. Once the preprotein emerges on the stromal side of the chloroplast protein import machinery, the transit peptide is cleaved by stromal processing peptidase. In the case of thylakoid-localized proteins, cleavage of the transit peptides may expose a second targeting signal guiding the protein to the thylakoid lumen or allow insertion into the thylakoid membrane by internal sequence information. This review summarizes the common features of targeting sequences and describes their role in routing preproteins to and across the chloroplast envelope as well as the thylakoid membrane and lumen.